Congress Handbook 37th IAHR World Congress: Managing Water for Sustainable Development Learning from the Past for the Future - IAHR, International Association for Hydro-Environment Engineering and Research; DID, Department of Irrigation and Drainage (Malaysia); REDAC, Pusat Penyelidikan Kejuruteraan Sungai dan Saliran Bandar (International Association for Hydro-Environment Engineering and Research, 2017)
The International Association for Hydro-Environment Engineering and Research (IAHR), founded in 1935, is a worldwide independent organisation of engineers and water specialists working in fields related to the hydro-environmental sciences and their practical application. Activities range from river and maritime hydraulics to water resources development and eco-hydraulics, through to ice engineering, hydro-informatics and continuing education and training. IAHR stimulates and promotes both research and it’s application and by doing so it strives to contribute to sustainable development, the optimisation of world water resources management and industrial flow processes.